GnRH-R targeted lytic peptide sensitizes BRCA wild-type ovarian cancer to PARP inhibition - Ma, Shaolin (Mol Cancer Ther, 2019)
EP-100 is a synthetic lytic peptide that specifically targets the gonadotropin-releasing hormone receptor on cancer cells. To extend the utility of EP-100, we aimed to identify effective combination therapies with EP-100 for ovarian cancer and explore potential mechanisms of this combination. A series of in vitro (MTT assay, immunoblot analysis, reverse-phase protein array, comet assay, and immunofluorescence staining) and in vivo experiments were carried out to determine the biological effects of EP-100 alone and in combination with standard-of-care drugs. EP-100 decreased the viability of ovarian cancer cells and reduced tumor growth in orthotopic mouse models. Of five standard drugs tested (cisplatin, paclitaxel, doxorubicin, topotecan, and olaparib), we found that the combination of EP-100 and olaparib was synergistic in ovarian cancer cell lines. Further experiments revealed that combined treatment of EP-100 and olaparib significantly increased the number of nuclear foci of phosphorylated histone H2AX. In addition, the extent of DNA damage was significantly increased after treatment with EP-100 and olaparib in comet assay. We performed reverse-phase protein array analyses and identified that the phosphoinositide 3-kinase/AKT pathway was inhibited by EP-100, which we validated with in vitro experiments. In vivo experiment using the HeyA8 mouse model demonstrated that mice treated with EP-100 and olaparib had lower tumor weights (0.06 ± 0.13 g) than those treated with a vehicle (1.19 ± 1.09 g), EP-100 alone (0.62 ± 0.78 g), or olaparib alone (0.50 ± 0.63 g). Our findings indicate that combining EP-100 with olaparib is a promising therapeutic strategy for ovarian cancer.